Standardized first aid knowledge test for candidates to the Trollhaugen Ski Patrol, Dresser, Wisconsin - Graff, Ruth (My University, 1978)
The purpose of this study was to construct a first aid knowledge test to be used to screen candidates to the Trollhaugen Ski Patrol. The test includes multiple choice questions covering all of the subject areas in the American Red Cross advanced first aid course. A pilot test was given to sixteen members of the Trollhaugen Patrol. On the basis of statisical analysis of this pilot test, a final test of one hundred questions was compiled.
Keywords: Skiing injuries.; Skiing accidents.